Optimalisasi Limbah Plastik dalam Produksi Paving: Upaya Penanggulangan Sampah Plastik Berkelanjutan - Bernandho, Aljo; Narastu, Rendy; Triatmaja, Aria (Fakultas Teknik Universitas Palangka Raya, 2025)
Plastic waste has become a major problem for the environment and public health in many places, including Warna Sari Village, Kapuas. Using a Community Development approach, the Palangka Raya University KKN Program Group 250 offers solutions through innovation to optimize plastic waste in paving production. A trial of paving made with a composition of 60% plastic, 30% oil, and 10% sand produced a product that is smoother, stronger, and lighter than conventional paving. The program also raises public awareness about plastic waste management and increases community participation. The results demonstrate technical, social, and economic benefits, as well as opportunities for local businesses. This could serve as a model for sustainable waste management that could be applied in other areas.